KONSEP DZIKIR MENURUT AMIN SYUKUR DAN RELEVANSINYA DENGAN TUJUAN PENDIDIKAN ISLAM - Siti Yumnah; Abdul Khakim (LP2M Universitas Ibrahimy, 2019)
Recitation as act of worship, according to Amin Syukur is a form of worship of beings, especially humans to Allah with the awareness of remembering Him. Where when remembrance involves between taste and brain simultaneously it will have a very extraordinary effect. The foundation of remembrance of Amen Gratitude is 4: remembrance qauly, zikir qalbi, remembrance of spirit and remembrance fi'ly. There are also 4 benefits of dzikir mentioned by Amin Syukur: (a) establishing faith (b) growing positive moral energy (c) avoiding danger and (d) as mental therapy. The relevance of remembrance with the aim of Islamic education according to Amin Syukur has a very close relationship. Remembrance is a way to make a person become a good, noble human being and of course remember his creation in this world which can lead people to become insan kāmil. Because it integrates the vision of faith, science and humanity where its formation is built through the process of Islamic education. Insan Kāmil without Islamic education will not be able to do the regeneration so that will result in the extinction of oneself (experiencing gaps even the disappearance of cadres who carried out the relay of the struggle of Insan Kāmil). On the contrary Islamic education without Insan Kāmil will not have a thing system that guarantees the birth of educational cadres who can take part in the future progress of life. The results of the research are expected can provide a reference for the education system so need attention for affective and psychomotor domains also.